2010
DOI: 10.2106/jbjs.i.00688
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of Measuring Femoral Anteversion and Neck-Shaft Angle in Patients with Cerebral Palsy

Abstract: A physical examination for determining femoral anteversion and the neck-shaft angle as measured on the internal rotation radiograph of the hips appear to be clinically relevant methods for evaluating the proximal femoral geometry and version in patients with cerebral palsy. Computed tomographic examination can probably be replaced by physical examination and an anteroposterior internal rotation radiograph of the hips for patients with stable hips who are able to walk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
72
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 32 publications
1
72
0
Order By: Relevance
“…Without controlling for the moderating effects of gross motor function, the association between femoral deformities and hip displacement cannot be clearly defined. Another problem is that measurement of femoral deformities, as seen on radiographs, could be affected by profound contracture and malposture in children with cerebral palsy who are nonambulatory [8,16]. With advancements in computerized image processing techniques, three-dimensional (3-D) CT has been proposed as a superior method to measure femoral deformities in children with cerebral palsy [1,4,7,11,13,18,23,32,34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Without controlling for the moderating effects of gross motor function, the association between femoral deformities and hip displacement cannot be clearly defined. Another problem is that measurement of femoral deformities, as seen on radiographs, could be affected by profound contracture and malposture in children with cerebral palsy who are nonambulatory [8,16]. With advancements in computerized image processing techniques, three-dimensional (3-D) CT has been proposed as a superior method to measure femoral deformities in children with cerebral palsy [1,4,7,11,13,18,23,32,34,35].…”
Section: Introductionmentioning
confidence: 99%
“…In general, the reliability of the neck-shaft angle has been shown to be good. A recent study of patients with cerebral palsy showed an overall intraobserver and interobserver reliability of neck-shaft-angle measurements on hip radiographs of 0.929 and 0.912, respectively 18 . Marmor et al found that neck-shaft-angle measurements varied <5°w ith <35°of limb rotation, and the measurements were always greater than the true value 19 .…”
mentioning
confidence: 99%
“…They found good inter & intra observer reliability in their methodology. Many western authors also observed good inter observer correlation in measuring NSA [31,32].…”
Section: Resultsmentioning
confidence: 86%